PENGARUH CORPORATE GOVERNANCE, BONUS PLAN, DAN FIRM SIZE TERHADAP MANAJEMEN LABA - Maduretno Widowati (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2013)
This study aims to obtain empirical evidence about the influence of corporate governance, bonus plans, and firm size on earnings management. Corporate governance is measured using two variables (independent commissioners state by the composition of an independent board and audit committee state by the number of audit committee members), bonus plans are measured from awarding compensation bonus by using a dummy, and firm size measured value of the final number of shares outstanding years. Earnings management measured by discretionary accruals using the Modified Jones Model. The population in this study were three companies engaged in the cement industry are listed in Indonesia Stock Exchange in 2007-2010. The research data obtained from the financial statements and annual reports of cement manufacturing firms in the period 2007-2010. Based on purposive sampling method, a sample of three companies by the number of observation data as much as 12 data derived from the company’s total multiplied by the sample period from 2007 to 2010. The hypothesis in this study were tested using multiple regression analysis. The analysis showed that the variables that have a significant influence on earnings management is variable of the audit committee, the bonus plan and firm size.